The Development, Formulation, and Assessment of Polyelectrolytic Complexes of an Anticancer Compound (Vinorelbine Tartarate) - Mohsen, Maged Mohammed Abdo; Nagasree, K.; Patil, Amit B. (Indian Journal of Pharmaceutical Education and Research, 2024)
Introduction Vinorelbine tartrate is used as a first-line treatment in conjunction with conventional treatments, especially advanced disease including cancer patients. Objectives The objective of the study was to develop a polyelectrolyte complex carrier system for Vinorelbine tartarate used for the treatment of Cancer. Materials and Methods Polyelectrolyte Complex (PEC) was prepared using entrapment method using gum Kondagogu and chitosan as polymers. Materials and Methods: Vinorelbine tartarate was best complexed with gum Kondagogu and chitosan. Various formulations were developed by changing the gum Kondagogu and chitosan ratios and optimized. The optimized formulations were further characterized for their complex formation, loading efficiency, entrapment efficiency, particle size, FTIR studies, in vitro release, swelling studies. Results At Gumkondagogu concentrations exceeding 80%, the highest output of PEC was noted. In comparison to phosphate buffer (pH 6.8), the PEC revealed a reduction in the discharge of vinorelbine tartarate in 0.1 N HCl. Increased medication release and swelling were caused by increasing the Kondagogu gum concentration in PEC. Due to chitosan’s greater degree of swelling in an acidic medium, PEC 1:3 (“Gumkondagogu: chitosan”) having a greater amount of chitosan demonstrated 98% release in just 4.5 hr. Conclusion The observation made in the present investigation conclusively proves that the novel hydrogels prepared from gum Kondagogu/chitosan holds a great potential as a natural polymer based delivery device for controlled delivery of drug like Vinorelbine tartarate for the reason to reduce dosing frequency.
Keywords: Anticancer agent; Polyelectrolyte complex; Vinorelbine tartarate; Gum Kondagogu and Chitosan